2022
DOI: 10.1186/s12944-022-01711-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential novel biomarkers in small intestine for obesity/obesity resistance revealed by multi-omics analysis

Abstract: Background Although obesity is caused by different factors, individual susceptibility to obesity differs among people under the same circumstances. The microbiota in the caecum or fresh faeces and metabolites in blood or urine contribute to obesity resistance; however, the microbiota or metabolites in the small intestine have not been extensively studied. Methods To investigate the relationship between the microbiota or metabolites in the small int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…Thus, they form a core functional subset that is associated with BW change and might be a potential regulatory target for the treatment of obesity. In a similar study, Pang et al ( 2022) also reported that Clostridium_sensu_stricto_1 is a biomarker in the gut microbiota for obesity resistance [54]. A high-ber diet selectively promotes the growth of SCFA-producing microbes [2,58], which was consistent with the current ndings.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, they form a core functional subset that is associated with BW change and might be a potential regulatory target for the treatment of obesity. In a similar study, Pang et al ( 2022) also reported that Clostridium_sensu_stricto_1 is a biomarker in the gut microbiota for obesity resistance [54]. A high-ber diet selectively promotes the growth of SCFA-producing microbes [2,58], which was consistent with the current ndings.…”
Section: Discussionsupporting
confidence: 84%
“…In this experiment, inulin mainly enhanced the generation of 5-hydroxy-ltryptophan (5-HTP), which is a precursor substance of serotonin that regulates a series of metabolic and psychological functions, in the metabolism of tryptophan [53]. In a previous study, 5-HTP was linked to weight loss by suppressing appetite [54], but this result is controversial. The bene ts of 5-HTP have mainly been shown to be anti-depressive by many studies [55].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, aging induced the upregulation of LPS-producing bacterial such as Bacteroidaceae and Bacteroides , which are at lower abundance in young mice. It has been demonstrated that a high abundance of Alistipes , Bacteroides , Clostridium_sensu_stricto _1, Colidextribacter and Lachnoclostridium was associated with dysbiosis, oxidative stress, obesity, chronic inflammation and neurodegenerative diseases, indicating that these microbes may increase the risk of the onset of chronic diseases and inflammation ( Zafar and Saier, 2021 ; Cai et al, 2022 ; Pang et al, 2022 ; Liu et al, 2023 ; Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nantong, Jiangsu, China). After 10 weeks, normal diet mice were continued to be fed after excluding the weight extremes (n = 14), and high-fat diet mice with a body weight (single mouse) of 20% (Buettner et al, 2007;Guo et al, 2020;Pang et al, 2022) or more of the mean body weight of CON group were selected for further studies. Compositions of the normal diet and high-fat diet are listed in Table 1.…”
Section: Animals and Dietsmentioning
confidence: 99%